Low Molecular Weight Sericin Enhances the In Vitro of Immunological Modulation and Cell Migration - Cherng, Juin-Hong; Chang, Shu-Jen; Chiu, Yaw-Kwan; Chiu, Yu-Hsiang; Fang, Tong-Jing; Chen, Hsiang-Cheng (Frontiers in Bioengineering and Biotechnology, 2022)
Sericin, a waste product of the silk textile industry, has favorable physicochemical and biological properties. In this study, we extracted a low molecular weight sericin (LMW-sericin; below 10 kDa) by performing high-temperature and high-pressure method and confirmed the MW using matrix-assisted laser desorption ionization-time of flight and liquid chromatography-mass spectrometry. Further, we determined its biological effects on macrophages and human adipose stem cells (hASCs) as cell models to investigate the biocompatibility, immunomodulation behavior, and potential signaling pathways-related wound healing via analyses of gene expression of focal adhesion and human cytokines and chemokines using quantitative real-time polymerase chain reaction and cytokine assay. LMW-sericin showed good biocompatibility both in macrophages and hASCs. Macrophages-cultured with 0.1 mg/ml LMW-sericin displayed an improved inflammatory response shown by the upregulation of CXCL9, IL12A, BMP7, and IL10, which developed Th1 and Th2 balance. LMW-sericin also improved the differentiation of macrophages toward the M2 phenotype by significantly enhancing the expression of Arg-1, which is conducive to the repair of the inflammatory environment. Moreover, the gene expression of hASCs showed that LMW-sericin promoted the secretion of beneficial adhesion molecules that potentially activate the gene transcription of differentiation and migration in hASCs, as well as significantly enhanced the levels of PKCβ1, RhoA, and RasGFR1 as fruitful molecules in wound healing. These findings provide insights into LMW-sericin application as a potential biomaterial for wound management.